2013
DOI: 10.1111/j.1600-048x.2013.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell spot scoring methods cannot be used as a reliable proxy to determine pigment quantity

Abstract: Eggshell maculation of most passerines is due to the deposition of the pigment protoporphyrin which is produced during biosynthesis of blood haem. Its functional signifi cance has only received empirical attention in recent years. Th is interest has generated a number of hypotheses of which some remain untested partly because the quantifi cation of protoporphyrin is analytically challenging and can be prohibitively expensive. Many studies have therefore used the extent of eggshell spotting as a proxy for total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Similar to our results, Holveck et al (2012) found that the spectral chroma of brown spots was significantly correlated with spot intensity and spot size, but not with spot distribution, in a French population of Great Tits. Brulez et al (2014) reported that eggshell protoporphyrin concentration was correlated with spot intensity and spot size, but not with spot distribution, in British Great Tits. However, the authors pointed out that correlations with pigment concentration were not sufficiently strong to be used as reliable surrogates, and in our study we found similarly moderate correlation coefficient values.…”
Section: Relationships Among Eggshell Pigmentation Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, Holveck et al (2012) found that the spectral chroma of brown spots was significantly correlated with spot intensity and spot size, but not with spot distribution, in a French population of Great Tits. Brulez et al (2014) reported that eggshell protoporphyrin concentration was correlated with spot intensity and spot size, but not with spot distribution, in British Great Tits. However, the authors pointed out that correlations with pigment concentration were not sufficiently strong to be used as reliable surrogates, and in our study we found similarly moderate correlation coefficient values.…”
Section: Relationships Among Eggshell Pigmentation Traitsmentioning
confidence: 99%
“…Others determined pigment concentration of the eggshell by chemical analysis (Maurer et al 2011b, Cassey et al 2012, Duval et al 2013, Brulez et al 2014, or analyzed digitized pictures of eggshells to determine the percentage of spotted eggshell surface (Martínez-de la Puente et al 2007, Sanz and García-Navas 2009, Bulla et al 2012, Holveck et al 2012, Brulez et al 2014), or to determine hue, saturation, and brightness derived from HSB and RGB (Martínez-Padilla et al 2010, Cassey et al 2012, Holveck et al 2012), or to determine other spotting pattern variables, such as pattern contrast and marking size (Stoddard et al 2012). Finally, many studies used visual scoring of photographs, and spotting pattern was expressed as spot intensity, spot size, and spot distribution (Gosler et al 2005, Sanz and García-Navas 2009, López de Hierro and De Neve 2010, Bulla et al 2012, Holveck et al 2012, De Coster et al 2013, Hargitai et al 2013, Brulez et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This is a novel and important finding with regard to the developmental biology of the quail (and presumably other Galliformes), suggesting that protoporphyrin may also be accumulated by way of an increase in eggshell thickness. Presumably, therefore, the absolute pigment content cannot be evaluated correctly by any attempt at a visual description of an eggshell's external pigmentation (e.g., Brulez et al 2014, Pike 2015. It thus appears that this overlooked mechanism of pigment deposition through a thickening of its layer can better explain some conflicting results published earlier-for example, that the greater number of visible brown spots on quail eggshells is not due to enhanced protoporphyrin deposition (Duval et al 2016).…”
Section: Discussionmentioning
confidence: 38%
“…Otsu algorithm has been widely used in previous related work such as approaches in Refs. 10,12,13,17 . This algorithm exhaustively searches for the threshold that minimizes the intra-class variance defined as a weighted sum of variances of the two classes.…”
Section: Experiments 4: Evaluating the Dynamic Threshold Finding Methodsmentioning
confidence: 99%
“…Some of the research is dedicated to the detection of cracks and dirt on eggs, 4,5,6,7,8,9,10,11,12,13 or measuring physical coordinates of eggs 5,11,14,15,16,17 . In a similar manner to the candling machines, most of these researches usually use light sources such as the incandescent lamp, fluorescent lamp or halogen lamp to back-illuminate the egg.…”
Section: Introductionmentioning
confidence: 99%